Urgensitas Olahraga Dalam Islam - Zuqriva Hayati; Ilian Ikhsan; Charles Charles (Pusat Studi Ilmu Keolahragaan, Fakultas Ilmu Keolahragaan, Universitas Negeri Padang, 2023)
This study discusses the concept and urgency of sports from an Islamic point of view and the legality of women in participating in world sports competitions. This descriptive qualitative research with literature review obtained a knowledge where in Islamic teachings it is highly recommended for a Muslim to maintain health, be it physical or physical health or spiritual or spiritual health. One of the methods used to maintain this health is by diligently sweating through sports, such as riding, swimming, soccer, and other sports while in accordance with Islamic provisions or sharia. As a result, both men and women from the point of view of Islam are fine if they want to exercise. Then in the case of discrimination that is often experienced by women in several sporting events, it turns out to be caused by the regulations applied by the organizers in these sports competitions. so that this dispels the opinion of other parties who state that Islamic teachings limit women in several ways, including the sports aspect.